SIFAT PAPAN WOL KAYU DARI 19 JENIS KAYU SULAWESI TENGAH - l M Sulastiningsih; Paribotro Sutigno; Rozak Memed (Jurnal Penelitian Hasil Hutan, 1987)
The results of laboratory test on the properties  of wood-wood  boards manufactured  from  19 individual  wood species obtained from  Central Sulawesi province  are reported in this paper.  The tests comprised board density,  moisture  content, thickness  reduction  due to compression  and bending strength.The results show an average yield  of  wood-wool  is 238 kg per cubic  meter  of  log  input.   Four wood  species  required presoaking  for wood-wool  making.  The physical  and mechanical properties  of  the wood-woo/  board  made from  seven wood species mineralized  with CaCl2 solution or Ca(OH2) suspension  meet DIN 1101 standard.